Castable refractory

CN116867753BActive Publication Date: 2025-01-10JFE STEEL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280014557.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-04-07
Filing Date
2022-04-07
Publication Date
2025-01-10
Estimated Expiration
2042-04-07

AI Technical Summary

Technical Problem

Existing castable refractories are prone to adhere to scale after curing, resulting in reduced effective volume and risk of steel leakage, and have poor corrosion resistance and slag penetration suppression effect.

Method used

Castable refractory containing calcined alumina, hydrophilic graphite, spinel and high alumina cement is used. The hydrophilic graphite content is 1 to 10%, the spinel content is 18 to 37%, and the high alumina cement content is 5. ~11%, the content of calcined alumina is less than 10%, and the content of magnesium sand is less than 8%. The combination of these components is suppressed by inhibiting scale adhesion and slag penetration.

Benefits of technology

It achieves sufficient strength and excellent corrosion resistance after curing, inhibits slag penetration and effectively prevents scale adhesion, and improves the use efficiency and safety of the ladle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116867753B_ABST
    Figure CN116867753B_ABST
Patent Text Reader

Abstract

Provided is a castable refractory which exhibits sufficient strength after solidification, has excellent corrosion resistance to slag, can inhibit slag penetration, and can inhibit scale adhesion. The castable refractory contains alumina including calcined alumina, hydrophilic graphite, spinel, and high-alumina cement, wherein the content of the hydrophilic graphite is 1 to 10% by mass, the content of the spinel is 18 to 37% by mass, the content of the high-alumina cement is 5 to 11% by mass, the content of magnesia is 8% or less by mass, and the content of the calcined alumina is 10% or less by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to castable refractory materials. Background Art

[0002] Generally, alumina-magnesia castable refractory is used as the lining of the ladle.

[0003] Sometimes, high-melting-point slag containing spinel (MgAl2O4) as a main component, called scale, adheres to the inner surface (lining surface) of such a ladle (hereinafter also referred to as "scale deposit").

[0004] In a ladle with scale deposited on the inner surface, the effective volume is reduced, and the processing volume per filling is reduced. In addition, during secondary refining, there is also a risk that the scale deposits will peel off along with the intact layer of the lining, causing steel leakage.

[0005] For example, Patent Document 1 discloses a technology for obtaining a "desired scale accumulation prevention effect" by using "dolomite composed of CaO (calcium oxide) and MgO (magnesium oxide)" in the lining of a ladle (

[0019] ).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2005-263516 Summary of the invention

[0009] Problems to be solved by the invention

[0010] As described above, scale may adhere to the solidified body of the castable refractory.

[0011] Furthermore, the castable refractory preferably exhibits sufficient strength after solidification, has excellent corrosion resistance to slag, and can suppress slag penetration.

[0012] Therefore, an object of the present invention is to provide a castable refractory which exhibits sufficient strength after solidification, has excellent corrosion resistance to slag, can suppress slag penetration, and can suppress scale adhesion.

[0013] Means for solving problems

[0014] As a result of intensive studies, the inventors of the present application have found that the above-mentioned object can be achieved by adopting the following configuration, thereby completing the present invention.

[0015] That is, the present invention provides the following [1] to [3].

[0016] [1] A castable refractory comprising: alumina including calcined alumina; hydrophilic graphite; spinel; and high-alumina cement, wherein the content of the hydrophilic graphite is 1 to 10% by mass, the content of the spinel is 18 to 37% by mass, the content of the high-alumina cement is 5 to 11% by mass, the content of magnesia is less than 8% by mass, and the content of the calcined alumina is less than 10% by mass.

[0017] [2] The castable refractory according to [1] above, wherein the hydrophilic graphite includes flaky graphite.

[0018] [3] The castable refractory according to [1] or [2] above, wherein the content of the calcined alumina is 1 mass % or more.

[0019] [4] The castable refractory according to [3] above, wherein the particle size of the calcined alumina is 20 μm or less.

[0020] Effects of the Invention

[0021] According to the present invention, it is possible to provide a castable refractory which exhibits sufficient strength after solidification, has excellent corrosion resistance to slag, can suppress slag penetration, and can suppress scale adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] [ Figure 1 ] is a cross-sectional view showing a ladle.

[0023] [ Figure 2 ] is a cross-sectional view showing the state in which molten steel is supplied to continuous casting.

[0024] [ Figure 3 ] is an enlarged cross-sectional view showing the steel bath portion 5 including the artificial graphite 11.

[0025] [ Figure 4 ] is an enlarged cross-sectional view showing the steel bath portion 5 including the scaly graphite 12. DETAILED DESCRIPTION

[0026] [Ladle]

[0027] First, based on Figure 1 and Figure 2 The ladle is described, and scale adhesion is also described.

[0028] Figure 1 1 is a cross-sectional view showing the ladle 1 .

[0029] The ladle 1 is a container for holding molten steel 7. The molten steel 7 is obtained by, for example, decarburizing molten iron in a converter (not shown). On the molten steel 7, slag 8 floats.

[0030] The ladle 1 has, from the outside, an iron cover 2, a permanent lining 3, and a lining (a cushion portion 4, a steel bath portion 5, and a slag line portion 6).

[0031] The liner is divided into a pad portion 4 located at the bottom of the ladle 1 , a steel bath portion 5 in contact with molten steel 7 , and a slag line portion 6 in contact with molten slag 8 .

[0032] Figure 2 It is a cross-sectional view showing a state where molten steel 7 is supplied to continuous casting.

[0033] Secondary refining for removing impurities from the molten steel 7 or adding additive elements is carried out in the ladle 1. Main secondary refining methods include RH (Ruhrstahl-Heraeus), LF (Ladle Furnace), and VOD (Vacuum Oxygen Decarburization).

[0034] The molten steel 7 after the secondary refining is extracted from a hole provided in the bottom of the ladle 1 (including the cushion 4), passes through the tundish 10, and is supplied to continuous casting.

[0035] However, if Figure 2 As shown, as the molten steel 7 is drawn out, the slag 8 separates from the position in contact with the slag line portion 6 and gradually descends while in contact with the steel bath portion 5 .

[0036] At this time, the refractory of the slag line portion 6 is not easy to wet with the slag 8, but generally speaking, the refractory of the steel bath portion 5 is easy to wet with the slag 8. Figure 2 As shown, the slag 8 may adhere to the surface of the steel bath 5 from above as the slag 8 descends. That is, the scale 9 may adhere to the inner surface of the ladle 1 (the surface of the steel bath 5 as the lining).

[0037] The effective volume of the ladle 1 to which the scale 9 is attached is reduced compared to the case where the scale 9 is not attached. Therefore, the processing amount of the molten steel 7 per filling is reduced.

[0038] Furthermore, when the molten steel 7 is subjected to secondary refining or is subjected to continuous casting, there is a risk that the scale 9 may be peeled off together with the intact layer of the steel bath 5 .

[0039] However, by using the castable refractory of the present invention for the steel bath portion 5 , adhesion of the scale 9 can be suppressed.

[0040] Furthermore, the steel bath portion 5 using the castable refractory of the present invention can exhibit sufficient strength, have excellent corrosion resistance to the slag 8 , and can also suppress the penetration of the slag 8 .

[0041] [Castable refractory]

[0042] The castable refractory of the present invention contains: alumina including calcined alumina, hydrophilic graphite, spinel, and high-alumina cement, wherein the content of the above-mentioned hydrophilic graphite is 1-10% by mass, the content of the above-mentioned spinel is 18-37% by mass, the content of the above-mentioned high-alumina cement is 5-11% by mass, the content of magnesia is less than 8% by mass, and the content of the above-mentioned calcined alumina is less than 10% by mass.

[0043] <Refractory Powder>

[0044] First, the refractory powder contained in the castable refractory of the present invention will be described.

[0045] Alumina

[0046] The castable refractory of the present invention contains alumina as refractory powder.

[0047] Examples of alumina include fused alumina, sintered alumina, and calcined alumina.

[0048] The content of alumina in the castable refractory of the present invention can be appropriately adjusted according to the contents of other components and the like.

[0049] The content of alumina in the castable refractory of the present invention is, for example, 40 mass % or more, preferably 44 mass % or more, and more preferably 48 mass % or more.

[0050] On the other hand, the content is, for example, 82 mass % or less, preferably 78 mass % or less, more preferably 74 mass % or less, and further preferably 70 mass % or less.

[0051] (Calcined Alumina)

[0052] As described later, the castable refractory of the present invention contains hydrophilic graphite and high-alumina cement.

[0053] The CaO in the high-alumina cement reacts with calcined alumina with a particle size of 20 μm or less at a high temperature of 1400°C or higher to generate CaAl 12 O 19 Such plate-like crystals (CaAl4O7+4Al2O3→CaAl 12 O 19 ), resulting in volume expansion. This is likely to occur when the amount of calcined alumina is large.

[0054] Usually, at high temperatures above 1400°C, Al2O3, MgO, CaO, SiO2, etc. react to form low-temperature melts and shrink during sintering. Therefore, volume expansion does not become a serious problem.

[0055] However, when the castable refractory contains hydrophilic graphite, since the hydrophilic graphite inhibits sintering, the volume expansion increases, and cracks are generated in the solidified body of the castable refractory.

[0056] Therefore, in the castable refractory of the present invention, the content of calcined alumina is reduced to suppress the occurrence of cracks due to volume expansion.

[0057] Specifically, the content of calcined alumina in the castable refractory of the present invention is 10% by mass or less, preferably 8% by mass or less, and more preferably 5% by mass or less.

[0058] On the other hand, the content of calcined alumina in the castable refractory of the present invention is, for example, 1 mass % or more, preferably 2 mass % or more, and more preferably 3 mass % or more.

[0059] The particle size of the calcined alumina is preferably 20 μm or less.

[0060] The “particle size” refers to a particle size at a cumulative value of 90% in a particle size distribution determined by a laser diffraction / scattering method in accordance with JIS R 1629 (1997) (the same applies hereinafter).

[0061] (Fused Alumina and Sintered Alumina)

[0062] The castable refractory of the present invention preferably contains, as alumina, at least one selected from the group consisting of fused alumina and sintered alumina.

[0063] The content of at least one selected from the group consisting of fused alumina and sintered alumina in the castable refractory of the present invention is, for example, 30 mass % or more, preferably 35 mass % or more, and more preferably 40 mass % or more.

[0064] On the other hand, the content is, for example, 75 mass % or less, preferably 70 mass % or less, and more preferably 65 mass % or less.

[0065] Hydrophilic Graphite

[0066] The castable refractory of the present invention contains hydrophilic graphite as refractory powder.

[0067] Hydrophilic graphite is difficult to be wetted by molten slag and has better oxidation resistance than pitch and carbon black. Therefore, the castable refractory of the present invention can suppress the adhesion of scale after solidification.

[0068] From the viewpoint of obtaining such effects, the content of the hydrophilic graphite in the castable refractory of the present invention is 1 mass % or more, preferably 2 mass % or more, and more preferably 3 mass % or more.

[0069] On the other hand, if the castable refractory contains too much hydrophilic graphite, the C concentration in the molten steel increases, and the decarburization blowing time increases.

[0070] Therefore, the content of the hydrophilic graphite in the castable refractory of the present invention is 10% by mass or less, preferably 8% by mass or less, and more preferably 5% by mass or less.

[0071] Whether a carbon material such as graphite is hydrophilic or not is determined by the following hydrophilicity evaluation test.

[0072] First, add 100 cc of distilled water (pure water) into a 100 cc beaker.

[0073] Next, weigh 10g of the carbon material sample and gently place it on the still water surface in the beaker. After 1 hour, after removing the carbon material floating on the water surface, put the beaker containing the carbon material settled in the water into a dryer to remove moisture. Measure the mass of the carbon material in the beaker after removing moisture (the mass of the settled sample).

[0074] The ratio of the mass of the precipitated sample to the mass (10 g) of the carbon material sample used in the test was determined as a sedimentation rate (unit: mass %).

[0075] When the sedimentation rate of the carbon material is 50.0 mass % or more, the carbon material is determined to be hydrophilic. On the other hand, when the sedimentation rate of the carbon material is less than 50.0 mass %, the carbon material is determined to be hydrophobic.

[0076] The results of the hydrophilicity evaluation test performed on various carbon materials (graphite, carbon black, coke powder, pitch) are shown in Table 1 below.

[0077] [Table 1]

[0078] Table 1

[0079]

[0080] As described later, when obtaining a solidified body of a castable refractory, first, water is added to the castable refractory and kneaded to obtain a clay slurry.

[0081] In the case where the graphite contained in the castable refractory is hydrophobic graphite, the graphite has little contact with water, so in order to ensure the fluidity of the clay slurry, a large amount of water layer is required between the graphites. That is, the amount of added water increases. As a result, in the obtained solidified body, the porosity (apparent porosity) increases, and various properties (strength, corrosion resistance to slag, etc.) may become insufficient.

[0082] In contrast, when the graphite contained in the castable refractory is hydrophilic graphite, graphite is easily compatible with water, so even if the added water is a small amount, a water layer is easily formed between the graphites, and good fluidity can be obtained. In this case, in the obtained solidified body, the porosity (apparent porosity) is reduced, and various characteristics (strength, corrosion resistance to slag, etc.) are excellent.

[0083] However, conventionally, whether or not a carbon material such as graphite is hydrophilic has been determined by the following test (also referred to as “conventional test”).

[0084] That is, in conventional tests, a carbon material is made into a sheet, and a water drop is placed on the sheet to measure the contact angle, or the speed at which water passes through the sheet is measured to evaluate whether the carbon material is hydrophilic.

[0085] However, for the carbon materials used in castable refractory materials, as mentioned above, compatibility with water is important, and therefore the inventors of the present application believe that it is appropriate to evaluate the hydrophilicity of the carbon material based on how much the carbon material sinks in water, and thus conceived the above-mentioned hydrophilicity evaluation test (even if the same carbon material is used, if the test conditions are changed, the obtained sedimentation rate will also change, so the test conditions are kept constant).

[0086] In fact, for example, the contact angles of scaly graphite and flake graphite measured by conventional experiments are 86.3° and 89.7°, respectively, and there is almost no difference between the two.

[0087] In contrast, as shown in Table 1, the sedimentation rates obtained in the hydrophilicity evaluation test were 99.0 mass % and 34.0 mass %, respectively, which were very different from each other. In addition, the obtained characteristics were also greatly different (see Table 2 described later).

[0088] Therefore, the effectiveness of the above-mentioned hydrophilicity evaluation test was confirmed.

[0089] As shown in Table 1 above, examples of the hydrophilic graphite include artificial graphite and scaly graphite.

[0090] Among them, scaly graphite is more preferable than artificial graphite for the reasons described below.

[0091] Figure 3 It is a cross-sectional view showing an enlarged view of the steel bath portion 5 including the artificial graphite 11 . Figure 4 It is a cross-sectional view showing an enlarged view of the steel bath portion 5 including the scaly graphite 12 .

[0092] like Figure 4 As shown, the flake graphite 12 is arranged in a manner such that its length direction becomes horizontal during construction. Therefore, the area A2 (see Figure 4) is greater than the contact area A1 of the artificial graphite 11 and the molten steel 7 (see Figure 3 Therefore, the scaly graphite 12 is more difficult to dissolve in the molten steel 7 than the artificial graphite 11.

[0093] For the steel bath portion 5 where hydrophilic graphite remains, the slag 8 ( Figure 3-4 (not shown) is not easy to penetrate, and can inhibit fouling 9 ( Figure 3-4 Such an effect can be obtained more effectively when using scaly graphite 12 which is difficult to dissolve in molten steel 7.

[0094] Spinel

[0095] Alumina and magnesia react at a temperature of, for example, 1300° C. or higher to generate spinel (Al 2 O 3 +MgO→MgAl 2 O 4 ).

[0096] The generated spinel is solid-dissolved with γ-Al2O3, and in the presence of CO gas, lattice defect spinel is generated. The MgO concentration of the lattice defect spinel is lower than that of the theoretical spinel (MgAl2O4), so the corrosion resistance to molten slag is worse than that of the theoretical spinel.

[0097] Therefore, the castable refractory of the present invention contains spinel (e.g., fused spinel, sintered spinel, etc.) as the MgO component from the beginning, rather than containing magnesia. In this case, lattice defect spinel is not easily generated. Therefore, the castable refractory of the present invention has excellent corrosion resistance to slag after solidification.

[0098] Here, for example, a castable refractory containing 7 mass % of a MgO component is considered.

[0099] Compared with the castable refractory of 7 mass % alumina-magnesia-5 mass % hydrophilic graphite, the melt loss can be reduced to 1 / 1.5 to 1 / 5 in the case of the castable refractory of 22 mass % alumina-spinel-5 mass % hydrophilic graphite.

[0100] The castable refractory of the present invention contains spinel corresponding to 5 to 10 mass % of the MgO component.

[0101] Specifically, the content of spinel in the castable refractory of the present invention is 18 mass % or more, preferably 23 mass % or more, more preferably 28 mass % or more, and further preferably 33 mass % or more, because of excellent corrosion resistance to slag.

[0102] On the other hand, when a castable refractory having too much spinel comes into contact with molten steel after solidification, slag tends to penetrate deeper, and in this case, when spalling occurs, the spalling thickness tends to increase.

[0103] Therefore, from the viewpoint of suppressing slag penetration, the content of spinel in the castable refractory of the present invention is 37 mass % or less, preferably 32 mass % or less, more preferably 27 mass % or less, and further preferably 22 mass % or less.

[0104] Magnesium

[0105] As described above, the castable refractory of the present invention contains spinel in place of magnesia.

[0106] Specifically, for the reason of excellent corrosion resistance to slag, the content of magnesia (e.g., sintered magnesia) in the castable refractory of the present invention is 8 mass % or less, preferably 5 mass % or less, more preferably 1 mass % or less, further preferably 0.5 mass % or less, particularly preferably 0.1 mass % or less, and most preferably 0 mass %.

[0107] 《Other refractory powders》

[0108] The castable refractory of the present invention may further contain other refractory powders in addition to the above-mentioned alumina, hydrophilic graphite and spinel.

[0109] As other refractory powders, for example, metal powders such as Si, Al, and Al-Si alloys; silica raw materials such as silica fume; silica / alumina raw materials such as clay; carbides such as SiC and B4C; and the like.

[0110] The content of other refractory powder in the castable refractory of the present invention is, for example, 5 mass % or less, preferably 3 mass % or less, more preferably 1 mass % or less, and further preferably 0.5 mass % or less.

[0111] Specifically, for example, the content of the metal powder is preferably 5 mass % or less, more preferably 3 mass % or less. The content of the silica raw material, the silica / alumina raw material and the carbide is preferably 1 mass % or less, more preferably 0.5 mass % or less.

[0112] <Adhesive>

[0113] Next, the binder contained in the castable refractory of the present invention will be described.

[0114] 《High Alumina Cement》

[0115] The castable refractory of the present invention contains high-alumina cement as a binder.

[0116] From the viewpoint of exhibiting sufficient strength after solidification, the content of high alumina cement in the castable refractory of the present invention is 5% by mass or more, preferably 6% by mass or more, and more preferably 7% by mass or more.

[0117] On the other hand, the content of high alumina cement in the castable refractory of the present invention is 11% by mass or less, preferably 10% by mass or less, because the castable refractory has excellent corrosion resistance to slag after solidification.

[0118] <Dispersant>

[0119] A dispersant may be added to the castable refractory of the present invention.

[0120] Examples of the dispersant include polycarboxylic acids, polyacrylic acids, polyether-based dispersants, and naphthalenesulfonic acid. These may be used alone or in combination of two or more.

[0121] The amount of the polycarboxylic acid added is preferably 0.75 to 2.50 parts by mass, more preferably 0.95 to 2.30 parts by mass, based on 100 parts by mass of the castable refractory of the present invention.

[0122] The amount of polyacrylic acid, polyether dispersant and naphthalenesulfonic acid added is preferably 0.05 to 0.15 parts by mass, more preferably 0.07 to 0.12 parts by mass, respectively, based on 100 parts by mass of the castable refractory of the present invention.

[0123] [Solid body]

[0124] First, water is added to the castable refractory of the present invention, and kneaded using a stirrer or the like to form a clay slurry. That is, a clay slurry is obtained.

[0125] The water to be added is not particularly limited, and for example, industrial water, tap water, etc. can be used.

[0126] The amount of water added is preferably 3 to 10 parts by mass, more preferably 4 to 7 parts by mass, based on 100 parts by mass of the castable refractory of the present invention.

[0127] The kneading time is appropriately set depending on the amount of the castable refractory to be kneaded, the type of stirrer to be used, and the like.

[0128] The clay slurry obtained by kneading is poured into a predetermined mold, ladle, etc. When poured into a ladle, a mold frame called a core is placed and vibration is applied appropriately. It can also be applied to blowing materials.

[0129] Then, the clay slurry is aged, and after being cured, the mold frame is removed. The aging time can be appropriately determined according to the composition of the clay slurry, etc. Then, it can be dried. The drying temperature and drying time can be appropriately adjusted.

[0130] Thus, a solidified body of a castable refractory can be obtained. By using such a solidified body as a steel bath portion of a ladle (see Figure 1 and Figure 2), which can inhibit the adhesion of scale to the steel bath.

[0131] Example

[0132] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited to the following Examples.

[0133] <Preparation of Castable Refractory>

[0134] The components (refractory powder and binder) shown in Table 2 below were put into a universal stirrer in the amounts (unit: parts by mass) shown in Table 2 below so as to give a total of 2.5 kg, and stirred for 1 minute to obtain a castable refractory.

[0135] To the obtained castable refractory, water and polycarboxylic acid were added in the blending amounts shown in Table 2 below, and the mixture was stirred for 3 minutes to obtain a clay slurry.

[0136] The details of some of the components shown in Table 2 below are as follows.

[0137] Sintered alumina (5-1mm): Sintered alumina with a particle size of 1 to 5 mm

[0138] Sintered Alumina (1-0mm): Sintered Alumina with particle size below 1mm

[0139] Calcined alumina: Calcined alumina with a particle size of less than 20 μm

[0140] ·Flake graphite: flake graphite with particle size of 0.18 to 1 mm

[0141] Artificial graphite: Artificial graphite with a particle size of 0.106 to 0.5 mm ("G30" manufactured by Chuetsu Graphite Industry Co., Ltd.)

[0142] ·Flake graphite: Flake graphite with a particle size of 0.106 to 0.5 mm

[0143] Spinel: fused spinel with particle size less than 1mm

[0144] Magnesia: sintered magnesia with particle size less than 1mm

[0145] <Evaluation>

[0146] The obtained castable refractory (clay slurry) was used to perform the evaluation described below. The results are shown in Table 2 below.

[0147] Bending Strength

[0148] The clay slurry was poured into a mold frame of 40×40×160 mm and vibrated for 30 seconds using a table vibrator. After one day, the mold was removed and the mixture was dried at 110° C. for 24 hours to obtain a test piece as a cured product.

[0149] The obtained test piece was used to perform a bending test in accordance with JIS R 2553: 2005 to determine the bending strength (unit: MPa). The larger the value, the more sufficient the strength can be evaluated.

[0150] 《Linear change rate and apparent porosity》

[0151] A test piece as a cured product was obtained in the same manner as above.

[0152] The obtained test pieces were subjected to heat treatment. Specifically, the obtained test pieces (except the test pieces of Comparative Example 1) were placed in a silicon carbide container together with coke powder and covered with a lid, and reduction calcined at 1400°C for 3 hours. The test piece of Comparative Example 1 was not placed in a silicon carbide container, but heated at 1400°C in the atmosphere for 3 hours.

[0153] Using the test piece after the heat treatment, the line change rate (unit: %) was calculated according to JIS R 2554:2005.

[0154] Then, using the test piece after the heat treatment, the apparent porosity (unit: %) was determined in accordance with JIS R 2205-1992.

[0155] 《Melt loss index and slag penetration thickness》

[0156] The clay slurry was poured into a trapezoidal column mold of 53 / 78×35×160 mm and vibrated for 30 seconds using a table vibrator. After one day, the mold was removed and dried at 110° C. for 24 hours to obtain a test piece as a cured product.

[0157] The following tests were performed using the dried test pieces.

[0158] Specifically, eight test pieces were grouped into one set, and an octagonal fence was made by bonding them with alumina mortar, and the fence was set inside a high-frequency induction furnace.

[0159] 6.8 kg of electrolytic iron was placed inside the fence made of the test piece, and the temperature was raised to 1650°C while nitrogen was passed through. Then, a reagent mixed with 4.4 g of iron oxide, 18.4 g of silicon dioxide, 49.2 g of aluminum oxide, 113.8 g of calcium oxide, and 14.2 g of magnesium oxide was added. The reagent was replaced every hour and kept for 3 hours. Then, steel was tapped.

[0160] The dimensional change of the most corroded part of each test piece before and after the test was measured, and the result was normalized by an index (melting loss index) with Comparative Example 1 being 100. The smaller the melting loss index, the better the corrosion resistance can be evaluated.

[0161] Then, for the less corroded parts of each test piece, Ca was analyzed using a fluorescent X-ray device to obtain the slag penetration thickness (unit: mm). The smaller the value, the more the slag penetration can be evaluated to be suppressed.

[0162] 《Thickness of dirt》

[0163] The clay slurry was poured into a mold frame of φ30×160 mm and vibrated for 30 seconds using a table vibrator. After one day, the mold was removed and the mixture was dried at 110° C. for 24 hours to obtain a test piece as a cured product.

[0164] The obtained test pieces were subjected to heat treatment. Specifically, the obtained test pieces (except the test pieces of Comparative Example 1) were placed in a silicon carbide container together with coke powder and covered with a lid, and reduction calcined at 1400°C for 3 hours. The test piece of Comparative Example 1 was not placed in a silicon carbide container, but heated at 1400°C in the atmosphere for 3 hours.

[0165] The following tests were performed using the test pieces after the heat treatment (including the test pieces of Comparative Example 1).

[0166] Specifically, first, 36 g of iron oxide, 36 g of silicon dioxide, 352.8 g of aluminum oxide, 162.8 g of calcium carbonate, and 34.8 g of magnesium oxide were put into a crucible made of magnesia sand, and the temperature was raised to 1650° C. in an electric furnace filled with nitrogen to melt them, thereby producing molten slag.

[0167] The test piece was immersed in molten slag and held for 1 hour before being lifted. After the lifted test piece was cooled to room temperature, it was cut in half along the longitudinal direction to find the scale thickness (unit: mm) at the part where the slag (scale) adhered the most. The smaller the value, the more it can be evaluated as being able to suppress scale adhesion.

[0168] [Table 2]

[0169] Table 2 (1 / 2)

[0170]

[0171] Table 2 (2 / 2)

[0172]

[0173] <Summary of evaluation results>

[0174] As shown in Table 2, in Comparative Example 1 containing no graphite (hydrophilic graphite), the value of the scale thickness was large, and the suppression of scale adhesion was insufficient.

[0175] In Comparative Example 2, which contains graphite (hydrophilic graphite) and a large amount of magnesia, the melting loss index is large and the corrosion resistance is insufficient.

[0176] In Comparative Example 3 in which the spinel content is small, the melting loss index is large and the corrosion resistance is insufficient.

[0177] In Comparative Example 4 in which the spinel content was high, the value of the slag penetration thickness was large, and the suppression of slag penetration was insufficient.

[0178] In Comparative Example 5 in which the content of high alumina cement was small, the value of flexural strength was small and the strength was insufficient.

[0179] In Comparative Example 6 containing a large amount of calcined alumina, after heating at 1400°C, the test piece expanded and cracked.

[0180] In Comparative Example 7 in which the content of high alumina cement was high, the melting loss index was large and the corrosion resistance was insufficient.

[0181] In Comparative Example 8, in which hydrophobic graphite was used instead of hydrophilic graphite, the apparent porosity value was large. The bending strength value of such Comparative Example 8 was small, and the strength was insufficient. In addition, the melting loss index was large, and the corrosion resistance was insufficient. In addition, the slag penetration thickness value was large, and the suppression of slag penetration was insufficient.

[0182] On the other hand, in Inventive Examples 1 to 8, the melting loss index was 100 or less, and the corrosion resistance was equal to or higher than that of Comparative Example 1.

[0183] In Inventive Examples 1 to 8, the values ​​of the scale thickness were smaller than those of Comparative Example 1, and the scale adhesion was sufficiently suppressed.

[0184] In Inventive Examples 1 to 8, the slag penetration thickness was smaller than that of Comparative Example 4, and the slag penetration was sufficiently suppressed.

[0185] Inventive Examples 1 to 8 had a greater value of bending strength than that of Comparative Example 5, indicating sufficient strength.

[0186] Among Invention Examples 1 to 8, when comparing Invention Example 1 and Invention Example 8, which differ only in the type of hydrophilic graphite, Invention Example 1 using flaky graphite has smaller slag penetration thickness and smaller scale thickness than Invention Example 8 using artificial graphite.

[0187] In Invention Examples 1 to 8, when Invention Example 1 is compared with Invention Example 2, as the spinel content increases, the melting loss index decreases. On the other hand, as the spinel content decreases, the slag penetration thickness value decreases.

[0188] In Invention Examples 1 to 8, when comparing Invention Example 1 with Invention Example 4, as the content of high alumina cement increases, the bending strength value increases. On the other hand, as the content decreases, the melting loss index decreases. This is also the case in the comparison results between Invention Example 5 and Invention Example 6.

[0189] Description of Reference Numerals

[0190] 1: Ladle

[0191] 2: Iron Sheet

[0192] 3: Permanent lining

[0193] 4: Pad

[0194] 5: Steel bath

[0195] 6: Slag line

[0196] 7: Molten Steel

[0197] 8: Slag

[0198] 9: Dirt accumulation

[0199] 10: Tundish

[0200] 11: Artificial graphite (hydrophilic graphite)

[0201] 12: Scaly graphite (hydrophilic graphite)

Claims

1. A castable refractory comprising: Alumina including calcined alumina; Hydrophilic graphite; Spinel; and High alumina cement, in, The content of the hydrophilic graphite is 1 to 10% by mass. The content of the spinel is 18-37% by mass. The content of high alumina cement is 5-11% by mass. The content of magnesia is 8% by mass or less, The content of the calcined alumina is 1 mass % or more and 10 mass % or less, The content of the silica raw material is 1% by mass or less, The hydrophilic graphite is a graphite having a sedimentation rate of 50.0% by mass or more obtained by the following hydrophilicity evaluation test. Hydrophilicity evaluation test: First, add 100cc of distilled water, i.e., pure water, to a 100cc beaker; next, weigh a 10g sample of graphite and gently place it on the still water surface in the beaker; after 1 hour, after removing the graphite floating on the water surface, place the beaker containing the graphite settled in the water into a dryer to dry and remove moisture; measure the mass of the graphite in the beaker after removing the moisture, i.e., the mass of the settled sample; and calculate the ratio of the mass of the settled sample to the sample mass of the graphite used in the test, i.e., 10g, as the sedimentation rate in mass %.

2. The castable refractory according to claim 1, wherein: The hydrophilic graphite includes flaky graphite.

3. The castable refractory according to claim 1 or 2, wherein: The particle size of the calcined alumina is less than 20 μm.

Citation Information

Patent Citations

  • Molten steel vessel, method for manufacturing steel using the same, and lining refractory

    JP2005263516A

  • Ladle-lining carbon-containing amorphous refractories

    JP1992050178A

  • Alumina-spinel prepared unshaped refractory for trough of blast furnace

    JP1997157044A

  • Long nozzle for continuous casting

    JP1999320049A